Gorenstein rings generated by strongly stable sets of quadratic monomials. Issue 5 (4th May 2022) - Fröberg, Ralf; Nicklasson, Lisa
Abstract: We characterize all Gorenstein rings generated by strongly stable sets of monomials of degree two. We compute their Hilbert series in several cases, which also provides an answer to a question by Migliore and Nagel.